2008
DOI: 10.1128/iai.00350-08
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Susceptibilities of C57BL/6 and A/J Mouse Strains toStreptococcus suisSerotype 2 Infection

Abstract: Streptococcus suis is an important swine and human pathogen. Assessment of susceptibility to S. suis using animal models has been limited to monitoring mortality rates. We recently developed a hematogenous model of S. suis infection in adult CD1 outbred mice to study the in vivo development of an early septic shock-like syndrome that leads to death and a late phase that clearly induces central nervous system damage, including meningitis. In the present study, we compared the severities of septic shock-like syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
91
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 49 publications
16
91
0
Order By: Relevance
“…In agreement with the findings of previous studies (20,21,26), patterns of bacterial burdens observed in spleen and liver were similar to those observed in blood samples, with no significant differences being detected among strains (data not shown). These results suggest that the increased virulence of S. suis ST7 cannot be explained by an increase in blood bacterial burden and that other factors account for its pathogenic potential.…”
Section: Difference In Virulence Among North American European Andsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with the findings of previous studies (20,21,26), patterns of bacterial burdens observed in spleen and liver were similar to those observed in blood samples, with no significant differences being detected among strains (data not shown). These results suggest that the increased virulence of S. suis ST7 cannot be explained by an increase in blood bacterial burden and that other factors account for its pathogenic potential.…”
Section: Difference In Virulence Among North American European Andsupporting
confidence: 82%
“…For cytokine and chemokine analysis, mice were euthanized at 6 h postinfection. The dose of infection and postinfection times were selected on the basis of our previous work (21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of clinical signs of meningitis was observed in 14% of the remaining infected mice between days 3 and 7 postinfection. The disease evolution was thus similar to that in previous studies (40,47,49). Blood bacterial loads were determined on days 1, 2, 3, and 4 postinfection.…”
Section: Different Features Of Protein-and Cps-specific Ab Responsesmentioning
confidence: 68%
“…Earlier studies using immunocompetent strains have indicated that mice exhibit a spectrum of resistance to bacterial infection linked to neutrophil recruitment (7,9,12). We hypothesized that genetic variation in the capacity of alveolar macrophage-mediated bacterial killing may also exist.…”
mentioning
confidence: 99%